The Effect of Problem Based Learning Model on Students' Creative Thinking Ability - Zulkarnaen Zulkarnaen; Suhirman Suhirman; Samsun Hidayat; Saiful Prayogi; Fitria Sarnita; Widia Widia; Fathurrahmaniah Fathurrahmaniah; Azra Fauzi; Lisda Ramdhani; Ni Nyoman Sri Putu Verawati (Postgraduate, University of Mataram, 2022)
This study aimed to explore the effect of the PBL model on students' creative thinking ability. A quasi-experimental study with 70 samples divided into experimental group and control group was carried out in this study. Data on students' creative thinking ability were collected using 8 items of essay test instruments that accommodate the creative thinking ability indicators. Descriptive analysis using the n-gain equation and statistical analysis using the ANOVA test were carried out to determine the improvement and effect of the treatment implemented on students' creative thinking ability. The results showed that the students’ creative thinking ability in the experimental group (n-gain: 0.72) was significantly different (p<0.05) in comparison with the control group (n-gain: 0.14). Based on the results of the study, it can be concluded that the PBL model has a significant effect on students' creative thinking ability